2017
DOI: 10.1371/journal.pone.0170389
|View full text |Cite
|
Sign up to set email alerts
|

Folate Transporters in Placentas from Preterm Newborns and Their Relation to Cord Blood Folate and Vitamin B12 Levels

Abstract: Folate deficiency during pregnancy has been related to low birth weight, preterm (PT) birth and other health risks in the offspring; however, it is unknown whether prematurity is related to low folate transport through the placenta due to altered expression of specific folate transporters. We determined placental expression (mRNA and protein concentrations by RT-qPCR and WB respectively) of specific folate transporters: RFC, PCFT/HCP1 and FOLR1 in chorionic (fetal) and basal (maternal) plates of placentas of P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 49 publications
0
22
0
1
Order By: Relevance
“…Deficiencies in one carbon metabolites have been associated with increased risk for a range of poor health outcomes, including vascular disease, megaloblastic anemia, and certain types of cancer in adults 7 . The consequences of deficiencies in one-carbon metabolism are even more pronounced during intrauterine development, as folate deficiencies have been associated with a range of pregnancy complications including preterm birth and neural tube defects 1 , 7 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Deficiencies in one carbon metabolites have been associated with increased risk for a range of poor health outcomes, including vascular disease, megaloblastic anemia, and certain types of cancer in adults 7 . The consequences of deficiencies in one-carbon metabolism are even more pronounced during intrauterine development, as folate deficiencies have been associated with a range of pregnancy complications including preterm birth and neural tube defects 1 , 7 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Folates are transferred from the mother to the fetus through the placenta via 3 specific transporters (RFC, FOLR1, PCFT/HCP1) 18 in addition to additional efflux transporters belonging to the ABC superfamily that are present in the human placenta 19 . In our laboratory, we have found that placental folate transport varies according to birth weight 20 and gestational age 21 . In addition, preterm newborns (32-36 weeks of gestation) had higher serum folate levels and lower vitamin B12 levels compared to serum concentrations in term newborns 21 .…”
Section: Transport Of Folate To the Fetusmentioning
confidence: 97%
“…In our laboratory, we have found that placental folate transport varies according to birth weight 20 and gestational age 21 . In addition, preterm newborns (32-36 weeks of gestation) had higher serum folate levels and lower vitamin B12 levels compared to serum concentrations in term newborns 21 . The same was observed in small term infants for gestational age (SGA) compared to adequate term gestational age (AGA) infants 20 .…”
Section: Transport Of Folate To the Fetusmentioning
confidence: 97%
“…Folate transfer to the fetus is mediated by the placental transporters folate receptor alpha and beta (FRα/β), proton coupled folate transporter (PCFT) and reduced folate carrier 1 (RFC1) [16,17]. FRα is the main folate transporter responsible for maternal-to-fetal transfer across the placenta (in both mice and humans) and works together with PCFT and RFC1 to control the uptake and release of folate [18][19][20]. PCFT is a high-affinity folate transporter and RFC1 mediates folate transport to the fetus via bi-directional transport [16,19,[21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Although there is limited information on bacterial production of inositol, it is absorbed in the SI [42]. Once absorbed from the maternal gut into the blood, these micronutrients are then transferred transplacentally to the fetus [15,18,43,44].…”
Section: Introductionmentioning
confidence: 99%